Service Quality and Students' Satisfaction of Management Department of Kanakai Multiple Campus - Bhattarai, Dilli Bahadur (Kanakai Journal, 2023)
Service quality is an important tool for increasing student satisfaction. This study examines the service quality of the management department of Kanakai Multiple Campus (KMC) from students’ perspective. It also examines the order of strength and relationship of service quality dimension as student satisfactions. The study was conducted among 52 bachelor-level students of management department of KMC located at Jhapa district of Nepal was taken as sample based on SERVEQUAL gap model developed by Parasuraman et al.(1985, 1988a), and used four likert scale and random sampling method was applied to collect data. Major Findings were compared with the main objective to measure the level of students’ satisfaction and factors that contribute the service quality in management department of KMC. The result of the study emphasizes on the improvement of service quality dimensions of management department of KMC so as to satisfy students and get strategic advantage in this competitive marketplace. This study contributes valuable insights for educational institutions seeking to optimize service quality and bolster their market positioning.